Distribution and Microplastic Pollution and Its Associated Heavy Metal Contamination from an Urban Canal: A Case Study of Saen Saeb Canal, Thailand - Eamrat, Rawintra; Taweesan, Achara; Pussayanavin, Tatchai (Naresuan University Journal: Science and Technology (NUJST), 2022)
Microplastics are emerging as a widespread environmental contaminant in all ecological systems, including the aquatic environment. This study examined the distribution of microplastics, and heavy metals extracted from microplastics, on the surface water of Saen Saeb canal. This canal is subjected to many human activities and has a large accumulation of garbage. Samples of microplastics were collected by a modified pump. The average microplastics concentrations were 479 p/m 3 or 0.0856 g/m 3 (size of 1-0.3 mm) and 261 p/m 3 or 0.0415 g/m 3 (size of 0.3-0.1 mm). The dominant colors of these microplastics were transparent-brown and transparent. These microplastics are related to land-based sources which break into secondary microplastics. Film and fiber/line were predominantly investigated in the surface water sample. Their chemical structures were analyzed by Fourier Transformed Infrared Spectroscopy (FTIR) which were confirmed to be polymeric with polypropylene (PP) and polyethylene (PE) being the most abundant. Heavy metals (cadmium, copper, lead, chromium and zinc) were also detected in the microplastics. Since this urban canal connects two main rivers which flow into the Gulf of Thailand, many aquatic organisms in the river might have an effect on this pollution. The results of this study showed that a strong recommendation to enforce the improvement of solid waste collection to prevent pollutants from entering the environment is necessary. Keywords: microplastics, Saen Saeb canal, heavy metal, plastic debris, FTIR